Effects of ancient Thai boxing on lower leg strengthening and balancing in knee osteoarthritis patients: A pilot study. - Katiyajan, N.; Nakmareong, S.; Yonglittthipaon, P.; Siritaratiwat, W.; Auvichayapat, P.; Sawanyawisuth, K.; Janyacharoen, T. (Chulalongkorn Medical Journal, 2023)
Background : Osteoarthritis (OA) is a condition in which the knee has been over used for a long time. The degeneration of the joint. Gingivitis is the time when the joint will hurt. There is a knee deformity. It could not put on weight bearing on the joint. As the cartilage is worn away, the bone forms spurs, areas of abnormal hardening. And fluid-filled pockets in the marrow know as subchondral cysts. Knee pain is relieved by rest and made worse by moving the joint or placing weight on it. For this reason, researchers were interested in studying the effects of ancient Thai boxing application that improves the strength of muscles in the lower leg and balance in osteoarthritis. Objectives : To investigate the effect of the ancient Thai boxing exercises on the lower extremities muscles and balance in patients with mild to moderate knee osteoarthritis. Methods : This is an experimental study on 20 males and female elderly subjects with an average age of 60.8 7.5 years. They were divided into two groups of 10 participants, i.e., the control group and the modified ancient Thai boxing exercise group (experimental group). All participants were interviewed for their baseline characteristics that were examined according to the inclusion criteria before signing in as research participants. Then they underwent the lower leg strengthening by five time sit to stand (FTSST) and balance (Berg balance scale; BBS and time up and go test; TUGT) prior to 4, 8 and 12 weeks after intervention. The modified ancient Thai boxing exercise group practiced modified ancient Thai boxing exercise for a period of 60minutes per session, 3 times per week for 12 weeks. Results : Lower leg muscular strength test results have been observed since week 4 after post-exercise. Five-time sit-ups have been found, Week 8 changes after exercise. The 3-meter walk-and-walk test showed a change in Week 8 after exercise. On the contrary, the control group showed no statistically significant difference between before and 4, 8 and 12 weeks after the intervention in all parameters. Conclusion : The ancient Thai boxing exercise can improve strength and balance in osteoarthritis.